Governance and Management Performance in Integrated Coastal Defense: Enhancing Community Resilience in Indonesia - Didit Herdiawan; Ahmadi Ahmadi (Penerbit Goodwood, 2025)
Purpose: This study aimed to bridge the gap between coastal defense management strategies and community resilience by adopting a strategic management perspective. Integrated Coastal Defense (ICD) is conceptualized as a strategic resource, whereas governance, management capacity, and social capital are treated as organizational capabilities influencing resilience outcomes. Methodology: A quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected from 350 respondents across the North Natuna Sea, Malacca Strait, and Sulawesi Sea, representing stakeholders involved in governance, maritime security, and community-based coastal management in the region. Results: The findings reveal that ICD significantly influenced governance and social capital (? = 0.52, p < 0.001), which in turn enhanced community resilience (? = 0.41, p < 0.01). ICD also has a direct effect on resilience (? = 0.29, p < 0.05), with governance and social capital partially mediating this relationship (? = 0.21, p < 0.01). The model explained 68% of the variance in resilience (R² = 0.68). Conclusions: Community resilience is enhanced when coastal defense strategies are supported by strong governance, effective management, and active stakeholder participation. Limitations: The cross-sectional design and reliance on perception-based data may limit the causal inference and generalizability beyond the Indonesian context. Contributions: This study integrates strategic resource theory and resilience frameworks, demonstrating that coastal defense effectiveness depends on the alignment between infrastructure and governance capabilities.